FUNCTIONAL STATE OF CARDIOVASCULAR AND DIGESTIVE SYSTEMS IN THE BODY OF STUDENTS DURING FITNESS TRAINING - Sogokon, O.A.; Donets, O.V.; Donets, I.M. (World of Medicine and Biology, 2020)
Examination of students engaged in modern fitness technologies is performed in the work and it is established that physical exercises effect the activation of internal systems’ work in the body. Analyzing the correlation of recreative fitness with students’ nutrition provides an opportunity to identify prospects for improving cardiovascular and digestive systems, improving general condition and achieving the desired student athletic performance. The study found that 92.5% of students were positive about the new content of training in modern fitness technology and only 7.5% said their attitude was uncertain. During the experiment, the dynamics of changes in the parameters of the cardiovascular and digestive systems’ functional state (experimental/control groups) were confirmed: the mean body weight decreased by 2.8 kg/1.5 kg, the pulse at rest decreased to 65.25 beats./min.+0.25/74.46 bpm+0.64; systolic pressure decreased to 112.75 mm Hg+0.35/118.21 mm Hg+0.79; diastolic pressure decreased to 72.21 mm Hg+0.39/76.57 mm Hg+0.43; the vital capacity of the lungs increased by 0.4 l/0.2 l, which is evidence of the cardiovascular system’s economic activity and confirms the feasibility of the applied methodology of health fitness technologies. Regarding the expediency of dietary change: 77% of students said they needed change, while 21% said they wanted it, and only 2% said they didn’t want to change their diet.